Predisposing Anatomy for Thoracic Outlet Syndrome and Functional Outcomes after Supraclavicular Thoracic Outlet Decompression in Athletes - David Jiang; Robert Weiss; Benjamin Lind; Omar Morcos; Cheong Jun Lee (Vascular Specialist International, 2024)
Purpose: This study aims to examine predisposing anatomic factors and subsequent post-decompression functional outcomes among high-intensity athletes with thoracic outlet syndrome (TOS). Materials and Methods : A single-institution retrospective review was performed on a prospective database of patients with TOS from 2018 to 2023 who had undergone operative decompression for TOS. Demographics, TOS characteristics, predisposing anatomy, operative details, and postoperative outcomes were examined. The primary outcome was postoperative return to sport. Secondary outcomes included vascular patency. Results : A total of 13 patients who were engaged in high-demand athletic activity at the time of their diagnosis were included. Diagnoses included 8 (62%) patients with venous TOS, 4 (31%) patients with neurogenic TOS, and 1 (8%) patient with arterial TOS. Mixed vascular and neurogenic TOS was observed in 3 (23%) patients. The mean age of the cohort was 30 years. Abnormal scalene structure was observed in 12 (92%) patients, and abnormal bone structures were noted in 4 (27%) patients; 2 (15%) with cervical ribs and 3 (23%) patients with clavicular abnormalities. Prior ipsilateral upper extremity trauma was reported in 4 (27%) patients. Significant joint hypermobility was observed in 8 (62%) patients with a median Beighton score of 6. Supraclavicular cervical and/or first rib resection with scalenectomy was performed in all patients. One case of postoperative pneumothorax was treated non-operatively. Ten (77%) patients returned to sport. Duplex ultrasonography showed subclavian vein patency in all 8 patients with venous TOS and wide patency with no drop in perfusion indices in the patient with arterial TOS. Conclusion : Athletes with TOS who required operative intervention had a high incidence of musculoskeletal aberrations and joint hypermobility. Supraclavicular decompression was associated with a high success rate, with overall good functional outcomes and good likelihood of patients returning to preoperative high-intensity athletics.